2021
DOI: 10.1021/acssuschemeng.0c07367
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-Based Guide to Predict the pH of Eutectic Solvents: Promoting an Efficient Design Approach for New Green Solvents

Abstract: The case of sustainable solvents is of great interest both academically and industrially. With research communities becoming more aware of the negative impacts of conventional organic solvents, a range of greener and more sustainable solvents have been developed to counter the harmful drawbacks associated with conventional solvents. Among these, eutectic solvents (ESs) attracted considerable attention for their "green" properties and have proven their usefulness as environmentally benign alternatives to classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 100 publications
(196 reference statements)
0
57
0
Order By: Relevance
“…Therefore, any change in the molecular structure can be quantified. By coupling the σ profile of DES-forming compounds with experimental data using model-generating methods such as multiple linear regression (MLR), piecewise linear regression (PLR), or artificial neural networks (ANNs), models for the description of DESs’ physicochemical properties can be developed [ 11 , 12 , 13 , 14 ]. In most studies, good model fitting of the literature viscosity, density, and pH values of the DESs was obtained [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, any change in the molecular structure can be quantified. By coupling the σ profile of DES-forming compounds with experimental data using model-generating methods such as multiple linear regression (MLR), piecewise linear regression (PLR), or artificial neural networks (ANNs), models for the description of DESs’ physicochemical properties can be developed [ 11 , 12 , 13 , 14 ]. In most studies, good model fitting of the literature viscosity, density, and pH values of the DESs was obtained [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…For all choline chloride based DESs, a linear decrease of pH value was observed with the increase in temperature, and as concerning the water influence, the increase in water content decreases the pH for the majority of DESs. However, there are DESs where the opposite was observed, for instance in ChCl-citric acid mixture [41]. The fast metal corrosion due to the rapid hydrogen evolution reaction in acidic DESs was demonstrated by Abbott et al [48], where it was shown that the corrosion rate (expressed in μm per year) for mild steel in oxaline was two orders of magnitude higher in comparison to reline and ethaline, whereas it was one order of magnitude higher for Ni.…”
Section: Protic Character Of Dessmentioning
confidence: 99%
“…The pH value of a DES depends on the ability of the DES's cation, anion, and HBD to act as proton acceptors and proton donors [40,41]. If HA is a protic hydrogen bond donor, then the protonation reaction in DES is HA + Y ⇌ HY + +A − (1) where Y represents the DES constituent [40,41].…”
Section: Protic Character Of Dessmentioning
confidence: 99%
See 1 more Smart Citation
“…DESs are commonly described as a mixture of two or more compounds that form upon mixing a liquid phase with a melting point far below that of its constituents [23][24][25]. It is anticipated that the formation of the DES occurs via a combination of entropy of mixing, van der Waals interactions, and hydrogen bonding, where one compound is considered a hydrogen bond donor (HBD) and the other is a hydrogen bond acceptor (HBA).…”
Section: Introductionmentioning
confidence: 99%